Results of the TOP Study: Prospectively Randomized Multicenter Trial of an Ex Vivo Tacrolimus Rinse Before Transplantation in EDC Livers. Issue 6 (June 2016) - Pratschke, Sebastian; Arnold, Hannah; Zollner, Alfred; Heise, Michael; Pascher, Andreas; Schemmer, Peter; Scherer, Marcus N.; Bauer, Andreas; Jauch, Karl-Walter; Werner, Jens; Guba, Markus; Angele, Martin K.
Abstract : Background: Organ shortage results in the transplantation of extended donor criteria (EDC) livers which is associated with increased ischemia-reperfusion injury (IRI). Experimental studies indicate that an organ rinse with the calcineurin inhibitor tacrolimus before implantation protects against IRI. The tacrolimus organ perfusion study was initiated to examine the effects of ex vivo tacrolimus perfusion on IRI in transplantation of EDC livers. Methods: A prospective randomized multicenter trial comparing ex vivo perfusion of marginal liver grafts (≥2 EDC according to Eurotransplant manual) with tacrolimus (20 ng/mL) or histidine-tryptophane-ketoglutarate solution (control) was carried out at 5 German liver transplant centers (Munich Ludwig-Maximilians University, Berlin, Heidelberg, Mainz, Regensburg) between October 2011 and July 2013. Primary endpoint was the maximum alanine transaminase (ALT) level within 48 hours after transplantation. Secondary endpoints were aspartate transaminase (AST), prothrombine ratio, and graft-patient survival within an observation period of 1 week. After an interim analysis, the study was terminated by the scientific committee after the treatment of 24 patients (tacrolimus n = 11, Control n = 13). Results: Tacrolimus rinse did not reduce postoperative ALT peaks compared with control ( P = 0.207; tacrolimus: median, 812; range, 362-3403 vs control: median, 652; range, 147-2034). Moreover, ALT ( P = 0.100), prothrombine ratio ( P = 0.553), and bilirubin ( P = 0.815) did not differ between the groups. AST was higher in patients treated with tacrolimus ( P = 0.011). Survival was comparable in both groups ( P > 0.05). Conclusions: Contrary to experimental findings, tacrolimus rinse failed to improve the primary endpoint of the study (ALT). Because 1 secondary endpoint (AST) was even higher in the intervention group, the study was terminated prematurely. Thus, tacrolimus rinse cannot be recommended in transplantation of EDC livers.